Accessibility of transportation to child‐welfare involved parents and the related impact on court‐ordered service participation. Issue 3 (6th January 2022) - Findley, Erin; Crutchfield, Jandel
Abstract: Families involved with Child Protective Services (CPS) face daunting steps to meet their service plan goals in the effort to achieve reunification with their children. Families who lack transportation access face additional barriers. This study explored Court Appointed Special Advocates, or CASA, volunteers' perspectives of the impact of transportation access on child welfare‐involved families' service participation. Semi‐structured interviews were conducted with nine CASA volunteers in a large city in a Southeastern state. Questions were asked regarding volunteers' experiences of transportation access for parents and children. Primary emphasis was placed on families' access to services. Three primary themes emerged in the data analysis: (1) challenges are wide‐ranging, exacerbated by transportation issues; (2) transportation linked to court‐ordered services success; and (3) practical recommendations stem from transportation justice. Interviews illuminated transportation challenges faced by families involved with CPS. The observed link between transportation inequity and CPS permanency outcomes warrants serious consideration in future research. Recommendations provide initial guidance to begin addressing disparities faced by these families.